Lead Speciation and Bioavailability in Apatite-Amended Sediments - Kirk G. Scheckel; Aaron G. B. Williams; Gregory Mc Dermott; David Gratson; Dean Neptune; James A. Ryan (Applied and Environmental Soil Science)
The in situ sequestration of lead (Pb) in sediment with a phosphate amendment was investigated by Pb speciation and bioavailability. Sediment Pb in preamendment samples was identified as galena (PbS) with trace amounts of absorbed Pb. Sediment exposed to atmospheric conditions underwent conversion to hydrocerussite and anglesite. Sediments mixed with apatite exhibited limited conversion to pyromorphite, the hypothesized end product. Conversion of PbS to pyromorphite is inhibited under reducing conditions, and pyromorphite formation appears limited to reaction with pore water Pb and PbS oxidation products. Porewater Pb values were decreased by 94% or more when sediment was amended with apatite. The acute toxicity of the sediment Pb was evaluated with Hyalella azteca and bioaccumulation of Pb with Lumbriculus variegatus. The growth of H. azteca may be mildly inhibited in contaminated sediment, with apatite-amended sediments exhibiting on average a higher growth weight by approximately 20%. The bioaccumulation of Pb in L. variegatus tissue decreased with increased phosphate loading in contaminated sediment. The study indicates limited effectiveness of apatite in sequestering Pb if present as PbS under reducing conditions, but sequestration of porewater Pb and stabilization of near-surface sediment may be a feasible and alternative approach to decreasing potential toxicity of Pb.